METHODS OF ISLAMIC STUDIES BASED ON RATIONALITY AND SCIENTIFICITY IN THE FIELD OF CONTEMPORARY SOCIAL SCIENCES - Widiana; Mohammad Kurjum (Jurnal Studi Islam, 2025)
This article examines the integration of rationality-based and scientific methods of Islamic study in the context of contemporary social sciences, with an emphasis on the relationship between revelation as a source of values and rationality as an instrument of interpretation, as well as scientific methods as a tool for testing the effectiveness of applying religious values to modern social realities. This study uses a qualitative approach based on literature review. The purpose of this research is to contribute to the development of social science research methodologies based on Islamic values, while bridging the gap between classical Islamic scientific traditions and modern scientific approaches. The results of the study show that this integration opens up opportunities for the formation of a more applicable social analysis model, namely that Islamic teachings do not stop at normative moral ideas, but become principles that can be translated into social policy. This can be seen in the example of data-based zakat management. However, this study also found that epistemological paradigm gaps and the dichotomy of knowledge remain major obstacles. Therefore, a more open academic culture, stronger methodological literacy, and cross-disciplinary collaboration are needed for this integration to be effective and have a real impact on society. Key words: Islamic studies, rationality, science, contemporary social sciences Abstrak: Artikel ini mengkaji integrasi metode kajian Islam berbasis rasionalitas dan scientific pada wilayah ilmu sosial kontemporer, dengan titik tekan pada relasi antara wahyu sebagai sumber nilai dan rasionalitas sebagai instrumen interpretasi, serta metode ilmiah sebagai alat untuk menguji efektivitas penerapan nilai agama pada realitas sosial modern. Penelitian ini menggunakan pendekatan kualitatif berbasis studi literatur. Tujuan dari penelitian ini yaitu untuk memberikan kontribusi terhadap pengembangan metodologi penelitian ilmu sosial yang berlandaskan nilai-nilai Islam, sekaligus menjembatani antara tradisi keilmuan Islam klasik dan pendekatan ilmiah modern. Hasil kajian menunjukkan bahwa integrasi ini membuka peluang pembentukan model analisis sosial yang lebih aplikatif yakni ajaran Islam tidak berhenti sebagai gagasan moral normatif, tetapi menjadi prinsip yang dapat diturunkan ke dalam kebijakan sosial. Hal ini terlihat pada contoh pengelolaan zakat berbasis data. Meskipun demikian, penelitian ini juga menemukan bahwa kesenjangan paradigma epistemologis dan dikotomi ilmu masih menjadi hambatan utama. Oleh sebab itu, diperlukan budaya akademik yang lebih terbuka, literasi metodologi yang lebih kuat, serta kolaborasi lintas disiplin agar integrasi ini dapat berjalan efektif dan berdampak nyata bagi masyarakat. Kata kunci: Kajian Islam, rasional, scientific, ilmu sosial kontemporer